HPM and ADM for partial differential equations - Biazar, Jafar; Goldoust, Fereshteh (International Journal of Applied Mathematical Research, 2013)
In this work, Homotopy Perturbation method and Adomian decomposition method are used to solve systems of partial differential equations. These methods are which are well known methods nowadays based upon perturbation and decomposition theories. Some examples are provided to show the ability of these methods.